42 Is entresto being under utilised in england?. (June 2018) - Perez, Carlos; Sotto, Imelda; Patel, Ketna; Singhal, Arvind; Sriranganathan, Danujan; Eftychiou, Stavros; Patel, Hitesh; Thornton, George; Asher, Alex; Qudah, Tareq; Malik, Tooba; Bhattacharyya, Sanjeev; et al.
Abstract : Background: The Prospective Comparison of ARNI [Angiotensin Receptor Neprilysin Inhibitor] with ACEI [Angiotensin-Converting Enzyme Inhibitor] to Determine Impact on Global Mortality and Morbidity in Heart Failure Trial (PARADIGM-HF) demonstrated in patients with a left ventricular ejection fraction of 40% or less who were symptomatic that Entresto was superior to enalapril with a 16% relative risk reduction of death from any cause and 20% relative risk reduction in cardiovascular death. These data were published in September 2014 and the use of Entresto was endorsed by the National Institute for Health and Care Excellence (NICE) in April 2016. We sought to determine whether these trial data and recommendations in national guidelines has impacted on prescriptions for Entresto in primary care in England. Methods: We conducted a comprehensive nationwide retrospective study. Data were obtained from the Prescription Cost Analysis system, which holds information on every prescription dispensed in the community in England, covering a population of more than 50 million people. We obtained data for relevant heart failure medications including Entresto. Results: Between Nov 2009 and Sept 2017 there was a linear increase in the use of angiotensin converting enzyme inhibitors (ACEi), angiotensin receptor blockers (ARB), betablockers and mineralocorticoid receptor antagonists (MRA). These results are displayed in Figure 1. There has been an increase in the use of Entresto but on a much smaller scale to the other heart failure medications. Conclusion: In the 18 months since NICE carried out a technology appraisal and approved the use of Entresto there has been an increase in prescriptions but these numbers are still dwarfed in magnitude by other heart failure medications. In September 2017 there were more than 600 times the number of prescriptions for ACEi compared to Entresto. Entresto is not indicated in all patients with left ventricular impairment but it seems likely that a large number of patients who may benefit from Entresto have not yet been switched. The development of local processes/protocols may accelerate the conversion from ACEi to Entresto in those who meet NICE criteria.